Clinical investigational studies for validation of a next-generation sequencing in vitro diagnostic device for cystic fibrosis testing. (June 2014) - Grosu, Daniel S; Hague, Lynda; Chelliserry, Manjula; Kruglyak, Kristina M; Lenta, Ross; Klotzle, Brandy; San, Jonathan; Goldstein, Wendy M; Moturi, Sharmili; Devers, Patricia; Woolworth, Julie; Peters, Eric; et al.
Abstract : Purpose: Clinical investigational studies were conducted to demonstrate the accuracy and reproducibility of the Illumina MiSeqDx CF System, a next-generation sequencing (NGS) in vitro diagnostic device for cystic fibrosis testing. Methods: Two NGS assays – a Clinical Sequencing Assay (Sequencing Assay) and a 139-Variant Assay (Variant Assay) – were evaluated in both an Accuracy Study and a Reproducibility Study, with comparison to bi-directional Sanger sequencing and PCR as reference methods. For each study, positive agreement (PA), negative agreement (NA), and overall agreement (OA) were evaluated. Results: In the Accuracy Study, the Sequencing Assay achieved PA of 99.7% including the polyTG/polyT region and PA of 100% excluding the region. The Variant Assay achieved PA of 100%. NA and OA were >99.99% for both Assays. In the Reproducibility Study, the Sequencing Assay achieved PA of 99.2%; NA and OA were both 99.7%. The Variant Assay achieved PA of 99.8%; NA and OA were both 99.9%. Sample pass rates were 99.7% in both studies for both assays. Conclusion: This is the first systematic evaluation of a NGS platform for broad clinical use as an in vitro diagnostic, including accuracy validation with multiple reference methods and reproducibility validation at multiple clinical sites. These NGS-based Assays had accurate and reproducible results which were comparable to or better than other methods currently in clinical use for clinical genetic testing of cystic fibrosis.